Efficacy and safety of Tripterygium glycosides as an add-on treatment in adults with chronic urticaria: a systematic review and meta-analysis - Ming Li; Yan Li; Lujing Xiang (Taylor & Francis Group, 2023)
AbstractContext Tripterygium glycosides (TG), a traditional Chinese medicine, has been used to treat chronic urticaria (CU) in China, and the evidence of TG for CU needs to be updated thoroughly.Objective To systematically evaluate the efficacy and safety of TG combined with H1-antihistamine (H1-AH) in adults with CU.Methods Eligible randomized controlled trials were searched in eight databases until May 31, 2022, including CNKI, WanFang, VIP, SinoMed, PubMed, Cochrane Library, Embase, and Web of Science. The search terms included urticaria, Tripterygium, Lei Gong Teng, and Leigongteng. Rev Man 5.3 and Stata 12.0 were used for statistical analysis.Results A total of 27 studies with 2788 patients were included. The pooled results showed that TG plus H1-AH was superior to H1-AH alone in cure rate (RR = 1.37, 95% CI = 1.15 to 1.63, p = 0.0003), total efficacy rate (RR = 1.40, 95% CI = 1.30 to 1.50, p < 0.00001), pruritus (MD = −0.32, 95% CI = −0.54 to −0.11, p = 0.003), wheal number (MD = −0.31, 95% CI = −0.55 to −0.07, p = 0.01), wheal size (MD = −0.32, 95% CI = −0.46 to −0.19, p < 0.00001), and the serum level of immunoglobulin E (SMD = −1.39, 95% CI = −2.42 to −0.36, p = 0.008). Moreover, adverse events between two groups were mild, and their incidences were not significantly different.Conclusions The combination of TG and H1-AH is a promising and safe treatment for adults with refractory CU. Further high-quality studies are needed to confirm the evidence.